Modernization of the Criminal Law System in Combating Transnational Crime in the Era of Globalization - Folman P Ambarita (Journal of Strafvordering Indonesian, 2026)
The development of globalization has driven the rise of transnational crime, which is cross-jurisdictional, organized, and exploits technological advances and the global financial system. This phenomenon poses a serious challenge to the national criminal law system, which is still fundamentally oriented towards the principle of territoriality and has not fully anticipated the dynamics of transnational crime. This study aims to analyze the criminal law regulations for transnational crime from the perspective of national and international law, and to examine the modernization of the criminal law system as an effort to strengthen the prevention of transnational crime in the era of globalization. The research method used is normative legal research with a statutory approach, a conceptual approach, and a comparative approach analyzed qualitatively. The results show that the regulation of transnational crime in the Indonesian criminal law system has been regulated through various sectoral laws such as the Narcotics Law, the Money Laundering Law, the Eradication of Terrorism Law, and the Eradication of Human Trafficking Law. These regulations represent a form of implementation of Indonesia's commitment to international legal instruments, however, there are still unclear norms, especially regarding cross-border jurisdiction, coordination between law enforcement agencies, and regulations regarding digital technology-based crimes. Modernization of the criminal law system is necessary through harmonization of national law with international standards, strengthening international legal cooperation, utilizing technology in law enforcement, and reformulating legal norms that are more adaptive to the development of transnational crime.